Addressing Preconception Behavior Change Through Mobile Phone Apps: Systematic Review and Meta-analysis - Loretta Musgrave; Kate Cheney; Edwina Dorney; Caroline S E Homer; Adrienne Gordon (JMIR Publications, 2023)
BackgroundPositive health behavior changes before pregnancy can optimize perinatal outcomes for mothers, babies, and future generations. Women are often motivated to positively change their behavior in preparation for pregnancy to enhance their health and well-being. Mobile phone apps may provide an opportunity to deliver public health interventions during the preconception period. ObjectiveThis review aimed to synthesize the evidence of the effectiveness of mobile phone apps in promoting positive behavior changes in women of reproductive age before they are pregnant (preconception and interconception periods), which may improve future outcomes for mothers and babies. MethodsFive databases were searched in February 2022 for studies exploring mobile phone apps as a prepregnancy intervention to promote positive behavior change. The identified studies were retrieved and exported to EndNote (Thomson Reuters). Using Covidence (Veritas Health Innovation), a PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) study flow diagram was generated to map the number of records identified, included, and excluded. Three independent reviewers assessed the risk of bias and conducted data extraction using the Review Manager software (version 5.4, The Cochrane Collaboration), and the data were then pooled using a random-effects model. The Grades of Recommendation, Assessment, Development, and Evaluation system was used to assess the certainty of the evidence. ResultsOf the 2973 publications identified, 7 (0.24%) were included. The total number of participants across the 7 trials was 3161. Of the 7 studies, 4 (57%) included participants in the interconception period, and 3 (43%) included women in the preconception period. Of the 7 studies, 5 (71%) studies focused on weight reduction, assessing the outcomes of reductions in adiposity and weight. Of the 7 studies, nutrition and dietary outcomes were evaluated in 2 (29%) studies, blood pressure outcomes were compared in 4 (57%) studies, and biochemical and marker outcomes associated with managing disease symptoms were included in 4 (57%) studies. Analysis showed that there were no statistically significant differences in energy intake; weight loss; body fat; and biomarkers such as glycated hemoglobin, total cholesterol, fasting lipid profiles, or blood pressure when compared with standard care. ConclusionsOwing to the limited number of studies and low certainty of the evidence, no firm conclusions can be drawn on the effects of mobile phone app interventions on promoting positive behavior changes in women of reproductive age before they are pregnant (preconception and interconception periods). Trial RegistrationPROSPERO CRD42017065903; https://tinyurl.com/2p9dwk4a International Registered Report Identifier (IRRID)RR2-10.1186/s13643-019-0996-6